Distal biceps hook test – Sensitivity in acute and chronic tears and ability to predict the need for graft reconstruction - Luokkala, Toni (Shoulder Elbow, 2019)
BACKGROUND: The aim of this study was to assess the sensitivity of distal biceps hook test – O’Driscoll hook test – in a retrospective series of acute and chronic distal biceps tendon tears and investigate the ability of the test to predict the need for graft reconstruction. METHODS: We retrospectively evaluated 234 consecutive distal biceps tendon tears operated in a single centre. The result of O’Driscoll hook test and perioperative findings of distal biceps were documented in standard fashion. RESULTS: The perioperative and O’Driscoll hook test data were available in 202 cases. The sensitivity for the distal biceps hook test was 78% in all tears and 83% in complete tears. The sensitivity was significantly lower in partial tears (30%) and in cases where lacertus fibrosus was found to be intact (45 %). When O’Driscoll hook test was positive and the delay from initial injury to operative intervention was eight weeks or more, there was over 75% probability of achilles tendon allograft reconstruction. When O’Driscoll hook test was negative, the probability of reconstruction even after 12 weeks’ delay was only 20%. DISCUSSION: O’Driscoll hook test is useful when establishing distal biceps tendon tear diagnosis, but a negative test does not exclude rupture. In delayed cases, a positive test may predict the need for reconstruction.